Lusaka water network pipe failure - T.W. Makondo; C.K. Wamukwamba (2001)
The Lusaka Water and Sewerage Company Limited (LWSC) is a private company providing water and sewerage services to the City of Lusaka. Lusaka is the Capital of Zambia and has an estimated population of 2.2 million people over a surface area of 360 square kilometers. The population growth rate of the City is estimated at 6.2%. Approximately 60% of the population lives in peri-urban areas while 40% live in conventional residential areas consisting of medium and low density areas. The need for a reliable and adequate water supply system is therefore, of great importance.